Macroscopic quantum tunneling and retrapping processes in moderately damped YBaCuO Josephson junctions - Massarotti, D.; Longobardi, L.; Galletti, L.; Stornaiuolo, D.; Rotoli, G.; Tafuri, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The moderately damped regime in a Josephson junction (JJ) is quite common in devices characterized by low critical currents and therefore by low Josephson energies. Measurements of switching current distribution (SCD) are a direct way of discriminating the phase dynamics also in the nontrivial case of moderate damping, which is going to be more and more common with advances in nano-patterning superconductors and in materials science finalized to build hybrid systems. We report on measurements of SCDs, both in thermal and quantum regime, on moderately damped YBaCuO grain boundary biepitaxial JJs. A direct transition from phase diffusion regime to macroscopic quantum tunnelling occurs at about 130 mK. The crossover to the quantum regime is tuned by the magnetic field and phase dynamics is described by a fully consistent set of junction parameters derived through numerical simulations.